INTEGRASI OVERALL EQUIPMENT EFFECTIVENESS (OEE) DAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) UNTUK MENINGKATKAN EFEKTIFITAS MESIN SCREW PRESS DI PT. BEURATA SUBUR PERSADA KABUPATEN NAGAN RAYA - Fitriadi Fitriadi; Muzakir Muzakir; Suhardi Suhardi (Jurnal Optimalisasi, 2018)
This study aims to identify the Integration of Overall Equipment Effectiveness (OEE) and Failure Mode And Effect Analysis (FMEA) to Increase the Effectiveness of Screw Press Machines at PT. Beurata Subur Persada Nagan Raya Regency. Based on the results of the study showed that the effectiveness of the Screw Press for PT. Beurata Subur Persada is still in the effective category with an average Overall Equipment Effectiveness value of 86.14 percent. This means that the screw press machine used is still very effective in the process of pressing the FFB. From the results of the analysis of the six big lose factor, it can be seen that Reduced speed losses is a very significant factor in the decline in OEE values on screw press machines with an average of 52.69% or with a time of 130.47 minutes. The results of the FMEA analysis show that the RPN value the biggest is 180 in the breakdown losses for the type of broken shift failure then the second largest is 120 in the reduced speed losses for the type of failure the engine speed is reduced. The results of the FMEA weighting with the largest RPN (risk priority number) for each category are 180 and 120. Based on these results it is necessary to propose improvements to reduce the breakdown losses and reduced speed losses in the highest repair priority, namely broken beds and reduced engine speeds. Overcoming these problems can be done by doing preventive maintenance on a regular basis once a week to prevent damage by dismantling the machine and re-installing and tightening or replacing new components.